Condition assessment of seismically isolated multi-span highway bridge bearings using recorded and simulated seismic responses. Issue 16 (December 2022) - Yunsong, Xu; Siringoringo, Dionysius M; Fujino, Yozo
This paper describes a study on the responses analyses of a seismically isolated multi-span highway bridge recorded during the 2011 Great East Japan (Tohoku) earthquake and assessment of isolation bearing condition based on the responses. During the earthquake, lateral pounding and locking between the side-stoppers and the upper steel plate of the isolation bearings were observed of several piers. Finite element model was employed to analyze the problem and scenarios of locked bearing on the piers were simulated. The study also presents a wavelet-based technique to detect the presence and location of locked bearing. Instantaneous frequency of continuous wavelet transform of girder and piers accelerations were employed to evaluate isolation bearing condition by identifying the occurrence of high-frequency filtering effect. Afterwards, bearing condition was characterized via statistical clustering technique. Accuracy and efficacy of the technique were verified in simulations using three-dimensional finite element model of the bridge. Results of simulations demonstrate that wavelet-based features can effectively characterize isolation bearings condition directly from seismic responses of girder and piers.